Penguatan Karakter Cinta Pertanian Sejak Dini melalui Edukasi Budidaya Tanaman Berbasis Praktik bagi Siswa Sekolah Dasar - Aksal Mursalat; Ahmad Mustanir; Sunandar Said; Nurjannah Nonci; Muliani Samiri; Muhammad Rais Rahmat Razak; Muhammad Faisal Saade; Jamaluddin Ahmad; Nuraini Kasman; Muhammad Hanafi; Syamsu Tang; Andi Astinah Adnan (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The declining interest of younger generations in the agricultural sector has become a major challenge to ensuring sustainable farmer regeneration in Indonesia. Therefore, introducing agriculture at an early age through experiential learning is essential to foster positive attitudes toward farming. This community service program aimed to strengthen elementary school students' agricultural appreciation through practice-based plant cultivation education. The program was implemented at SD Negeri 3 Betao, Sidenreng Rappang Regency, involving 23 students. A participatory approach based on the learning by doing concept was applied through three stages: preparation, educational sessions integrated with hands-on plant cultivation activities, and monitoring and evaluation. Program effectiveness was assessed using pre-test and post-test questionnaires to measure changes in students' agricultural appreciation. The results demonstrated active participation from all students throughout the program. The average pre-test score increased from 52.1% to 92.6% in the post-test, representing an average improvement of 40.5%. Improvements were observed across all evaluation indicators, including enjoyment of planting activities, willingness to care for plants, appreciation of the farming profession, responsibility for maintaining planted crops, and interest in participating in future agricultural activities. These findings indicate that practice-based plant cultivation education is an effective approach to fostering agricultural appreciation among elementary school students and may contribute to supporting future farmer regeneration.